Pendampingan dan Pelatihan Pemasaran Digital pada UMKM Roti Desa Rengas Sumatera Selatan: Digital Marketing Assistance and Training at the Bakery Micro Small Medium Enterprise, Rengas Village, South Sumatra - Fatimah, Fatimah; Ghiffari, Ahmad; Herudiansyah, Gumar; Gusmiatun, Gusmiatun; Kasra, Helwan; Nawawi, Sulton (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Marketing strategies are needed to increase sales of bakery products. Labeling and packaging capabilities, as well as the use of innovative marketing methods, are still lacking among MSME Partners. The team is trying to increase the potential of MSME products with digital marketing training and food variants. The activity method is in the form of assisting students and teams in the 61st Muhammadiyah University of Palembang Real Work Lecture (KKN) program in Rengas I Village. This program includes identifying needs, planning, implementing and using various innovation materials as well as the Instagram and Facebook platforms. This activity takes the form of assistance from February to April 2024. Various variations of flavors and bread toppings are produced, then pictures and videos have been posted on digital marketing on Instagram and Facebook. The conclusion shows that support for MSMEs has a positive impact on the production of various types of bread. It is necessary to find out more about other social media platforms, such as TikTok and Twitter, in order to understand more efficient digital marketing strategies related to consumer behavior and preferences.